Analisis Disiplin Kerja Pegawai di Kantor Lembang Sikuku Kecamatan Kapala Pitu Kabupaten Toraja Utara - Yulianus Toban; RandiTangdialla RandiTangdialla; Althon K. Pongtuluran (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2026)
This study aims to analyze the dynamics of employee work discipline at the Lembang Sikuku Office, Kapala Pitu District, North Toraja Regency. Utilizing a descriptive qualitative approach, the focus of the study was explored based on three main dimensions: attendance, work attitudes and behavior, and organizational responsibility. Data were collected through in-depth interviews with six key informants, participatory observation, and documentary analysis, and were subsequently analyzed using data reduction, data display, and conclusion drawing techniques. The results indicate that employee work discipline is generally in a fairly good category, although it is still influenced by cultural flexibility. Regarding attendance, daily compliance is adequate, even though lateness and absenteeism still occur due to community activity preferences, family role conflicts, and health reasons. In terms of attitudes and behavior, employees demonstrate good compliance with leadership instructions and internal regulations, despite experiencing routine work fatigue. Regarding responsibility, main duties and public service functions are executed according to operational procedures, supported by harmonious interpersonal coordination. This study concludes that enforcing discipline in village governance requires a shift from paternalistic administrative control toward a consistent reward-and-punishment system to optimize public service quality.